Determination of sprayer parameters for fruit nurseries - R. М. Tavasiev; A. P. Dzitsoev; A. Ahmad (Сельскохозяйственные машины и технологии, 2024)
The paper highlights that in industrial plantings, pests and weeds control is conducted using sprayers. To establish the required liquid fl ow rate, it is necessary to use calculations for sprayer adjustment. A small-sized, remotely controlled «GNOM» unit, developed at Gorsk Agrarian University, is designed for various tasks, including herbicidal spraying in fruit nurseries. (Research purpose) The research aims to substantiate the optimal parameters of the spraying unit in the herbicide treatment module. It also seeks to investigate the dependence of the flow rate of the working fluid and quality of liquid spray on the pressure in the system. (Materials and methods) A laboratory installation was developed to study the spray characteristics. Nylon threads with diameters of 100 and 250 micrometers were placed within the spray zone, and the resulting liquid spray was captured using a Nikon COOLPIX 58100 digital camera. Each subsequent experiment was carried out at a liquid pressure of 0.05 megapascals more than the previous one. (Results and discussion) The experiments resulted in obtaining images of the spray swath for a small-sized self-propelled unit, allowing for the categorization of the spray based on droplet sizes. The theoretical analysis demonstrated how changes in the air volume within the tank influence both the pressure and quality of the liquid spray. Additionally, it showed how the dispersion depends on the pressure of the working fluid. (Conclusions) The analysis of the working fluid spray showed that at a pressure in the hydraulic system in the range from 0.65 to 0.75 megapascals and a spray angle of 90 degrees, the highest quality fine spray is observed, the flow rate of the working fluid is in the range of 0.4-0.6 liters per minute, which very signifi cantly affects the size of the treated area in the direction of its increase at one tank refueling unit.